PREVALENCE AND RISK FACTORS OF TRICHURIS SPP. ON GOATS IN DENPASAR CITY - Putri, Ketut Ayu Cudemani; Apsari, Ida Ayu Pasti; Nindhia, Tjok Sari (Buletin Veteriner Udayana, 2022)
Goats are animals that are susceptible to parasitic diseases, one of which is Trichuris spp . The purpose of this study was to determine the prevalence and risk factors for the infections of Trichuris spp . on goats kept in Denpasar city. In this study, 100 feces samples were taken from several breeders in the city of Denpasar, then data were recorded such as age, sex, number of goats per cage, breed, and also the housing system. The method used in this study is the floating method by taking 3 grams of feces, the homogenized and centrifuged at 1500 rpm for 5 minutes. Do it again after disposing of the supernatant. After centrifuged add saturated salt and let stand for 2-3 minutes and do the examination under the microscope and then the data were analyzed using bivariate analysis in the form of chi-square test. The result of this study found that the prevalence of Trichuris spp . by 95 and influenced by age and breed.